CONCERNING THE BONE CARVING IN ANCIENT VYSHGOROD (City: History, Culture, Society, 2020)
The article deals with the analysis of the state of local bone carving and introduction it into scientific circulation. The article introduces bone and antler products from Old Rus Vyshgorod into the scientific circulation and analyzes the level of development of local bone carving. All analyzed materials are dated back from 11th to 12th century. All bone products can be divided into two large groups. The first one includes primitive products of bone with minimal processing fully or partially based on the form of the source material. The second group consists of products made from prepared parts of a bone or antler. They have specific forms that are not related to the source material. The first group prevails by the number of finds. Primitive implements with a pointed working part were found most of all. The first group also includes playing astragals, a toy-bone with two holes (a device for reproducing noisy sounds), skates, amulets of wild boar and bear fangs. The second group includes things of different functional purpose (buttons, combs, knife handles, halter clasp, icon, egg-like product, chess piece, etc.). Separate semi-finished products and stocks were also identified. Bone products could appear in the life of the population of ancient Vyshgorod in two ways. In Vyshgorod, sporadic bone-carving work could occur. A small bone-carving workshop was discovered. Some of the productsmost difficult to manufacture could come from Kyiv, where professional bone carving craft was developed. Studying Vyshgorod is further evidence of uneven development of bone carving in different centres of Kyivan Rus, previously traced in the other Ancient Rus sites.
Keywords: Middle Dnipro region; Kyivan Rus; Vyshgorod; bone carving; bone and antler products